CML ENGAGEMENT IN ENGLISH COMPETENCY FOR TVET EDUCATORS - Nor Yazi, Khamis; Noor Raha, Mohd Radzuan (Pusat Bahasa Moden (PBM), 2024)
From May 6-10, 2024 – A team of 10 English language instructors of the Centre for Modern Languages (CML) engaged with 26 Kolej Kemahiran Tinggi MARA Kuantan (KKTM) in the English Competency Training. The training, which was carried out at KKTM Kuantan Perpustakaan Al Jazari and Smart Classroom, aims to improve understanding and mastery of the English language to improve the KKTM technical instructors’ teaching and learning quality in the Technical and Vocational Education and Training (TVET) arena.